An online communicative translation assessment model in an Indonesian EFL translation class: Students perceptions - Soni Tantan Tandiana; Fuad Abdullah; Dede Anwar; Emmas Maspupah (Universitas Syiah Kuala, 2025)
Translation studies have grown enormously in recent decades and have expanded to include the pedagogical lens as a breakthrough. However, little is known about how the students perceive the online communicative translation assessment model (OCTAM). The present study explores how the students perceive the implementation of the online communicative translation assessment model in classrooms. The investigative locus of this study was a class on Translating and Interpreting (TI) at a state university in Tasikmalaya, West Java, Indonesia. Thirteen students from a TI class participated in this study. The data were obtained from semi-structured interviews and analysed using a thematic analysis. The findings revealed that OCTAM provided students with an effective translation assessment model, coped with their limited English vocabulary, guided them to focus on knowledge of form, function, and meaning of both source and target texts, offered them a more contextual translation test, raised their awareness of translating as a meaning-making practice, facilitated them to correct grammatical errors, created a less anxious test atmosphere, and generated their multimodal communicative competence. Pedagogically, this study bridges translation and foreign language education, mainly by examining how an online communicative translation assessment model functions as a cutting-edge translation model to assess students translation competence.